Visual Immersion and Narrative Consistency Through Brand Engagement to Customer Emotional Connection on EB Batik - Sabrina Diva Amaliah; Ramlah Puji astuti (Mabsya: Jurnal Manajemen Bisnis Syariah, 2026)
This study examines the influence of visual immersion and narrative consistency on customer emotional connection in EB Batik MSMEs, with brand engagement as a mediating variable. Motivated by the phenomenon of low audience interaction despite substantial followers, this research underscores the importance of cultivating emotional bonds. Employing the Stimulus-Organism-Response (SOR) framework, visual immersion and narrative consistency are conceptualized as stimuli, brand engagement as the organism, and customer emotional connection as the response. A quantitative causal-associative approach was utilized involving 200 active social media users familiar with EB Batik. Questionnaire data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Findings reveal that visual immersion (β=0.473) and narrative consistency (β=0.319) exert positive and significant effects on brand engagement. Both variables also demonstrate direct and significant influences on customer emotional connection. Brand engagement proved to be a significant mediator in this relationship (β=0.185). The Adjusted R² value of 0.729 indicates that 72.9% of the variance in customer emotional connection is explained by the model. The implications emphasize that curating immersive visual experiences and maintaining consistent narratives constitute key strategic approaches to fostering engagement, ultimately serving as the foundation for establishing enduring customer emotional connections.